QUALITY OF HEALTH SERVICE THROUGH THE APPLICATION OF CITIZEN’S CHARTER INPUBLIC HEALTH CENTER TANAH KALIKEDINDING SURABAYA - SITI AMINAH (Universitas Negeri Surabaya, 2013)
QUALITY OF HEALTH SERVICE THROUGH THE APPLICATION OF CITIZEN’S CHARTER INPUBLIC HEALTH CENTER TANAH KALIKEDINDING SURABAYASITI AMINAHDra. MEIRINAWATI, M.AP.ABSTRACTThe bad quality of health services are still being felt by the public until now,encourage the government to further improve the quality of service. These effortsmanifested in the form of Citizen's Charter. Citizen's Charter is a service contract thatcontains an agreement between the service provider with service users about thetime, type, cost, procedure and manner of service delivery. The Embodiment ofCitizen's Charter to make health service delivery needs and interests of patients as themain thing in the whole service process, so the quality of health service can be realizedalong with the high patient satisfaction.This study uses descriptive research with a qualitative approach. The subjects ofthis study consisted of head of the public health centers, public health workers andpatients as users of the service with the snowball sampling method. Data collectiontechniques used in the form of interviews, observation and documentation. Dataanalysis was performed with data collection, data reduction, data display, andconclusion.This study describes the results of quality of health service through the applicationof the Citizen's Charter which can be seen from Tangibles indicator that shows thathealth service facilities in public health centers Tanah Kalikedinding is quite completeand in accordance with the needs of patients, Realibility shows that the hours ofservice that long completion time and cost of pelayananan health services are inaccordance with the provisions of the Citizen's Charter. Responsiveness shows Publichealth center Kalikedinding Surabaya conducted a survey for patients aimed todetermine the level of patient satisfaction, Assurance shows that the health centeremployee competence is good enough and the compensation can improve patientsatisfaction, Empathy shows that the service flow is easy to understand and complaintsunit to increase community participation in health service delivery. So it can beconcluded that through the implementation of Citizen's Charter, the quality of healthservices at the health center Kalikedinding country become better. Advice can be givenare: Citizen's Charter document should be attached to the wall and and shouldcompletion time of service must be timely.Keywords: Quality of Service, Service of health, Citizen’s Charter